Assessment of nonischemic fibrosis in hypertrophic cardiomyopathy: Comparison of gadopentetate dimeglumine and gadobenate dimeglumine for enhanced cardiovascular magnetic resonance imaging. Issue 5 (22nd October 2013) - Rudolph, Andre; von Knobelsdorff‐Brenkenhoff, Florian; Wassmuth, Ralf; Prothmann, Marcel; Utz, Wolfgang; Schulz‐Menger, Jeanette
Abstract : Purpose: To compare whether the higher relaxivity contrast agent gadobenate is superior for the identification of nonischemic late gadolinium enhancement (LGE) in hypertrophic cardiomyopathy (HCM) compared to standard relaxivity agents such as gadopentetate. Materials and Methods: Fifteen patients with HCM and positive LGE based on routine cardiac magnetic resonance (CMR) with 0.2 mmol/kg gadopentetate were enrolled. Each patient thereafter underwent a second enhanced CMR exam with 0.2 mmol/kg gadobenate using the same CMR protocol. LGE was assessed in a short axis stack acquired after contrast administration using an inversion recovery gradient echo sequence. Two independent blinded readers quantified LGE by manual planimetry. The signal intensities of injured myocardium, remote myocardium, left ventricular cavity, and air were measured in identical locations using anatomical landmarks and dedicated software. The signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) were calculated. Results: No adverse events related to contrast administration occurred. Gadobenate dimeglumine showed a higher SNR of injured myocardium (45.4 ± 24.0 vs. 31.1 ± 16.6, P = 0.002) and a higher CNR between remote and injured myocardium (37.6 ± 25.0 vs. 26.5 ± 17.6, P = 0.006) compared to gadopentetate dimeglumine. The amount of LGE (based on the same postprocessing criteria and definitions) was higher with gadobenate dimeglumine (12.7 ± 8.5 g vs. 9.4 ± 5.6 g, P = 0.005). There was no difference in intra‐ and interobserver variability between gadopentetate dimeglumine and gadobenate dimeglumine. Conclusion: CMR with the high relaxivity contrast agent gadobenate dimeglumine reveals significantly more tissue with LGE in patients with HCM.J. Magn. Reson. Imaging 2014;39:1153–1160 . ©2013 Wiley Periodicals, Inc .